Resilient Leaf Physiological Response of European Beech (Fagus sylvatica L.) to Summer Drought and Drought Release - Pflug, Ellen E.; Buchmann, Nina; Siegwolf, Rolf T. W.; Schaub, Marcus; Rigling, Andreas; Arend, Matthias (Frontiers in Plant Science, 2018)
Drought is a major environmental constraint to trees, causing severe stress and thus adversely affecting their functional integrity. European beech (Fagus sylvatica L.) is a key species in mesic forests that is commonly expected to suffer in a future climate with more intense and frequent droughts. Here, we assessed the seasonal response of leaf physiological characteristics of beech saplings to drought and drought release to investigate their potential to recover from the imposed stress and overcome previous limitations. Saplings were transplanted to model ecosystems and exposed to a simulated summer drought. Pre-dawn water potentials (ψpd), stomatal conductance (gS), intercellular CO2 concentration (ci), net-photosynthesis (AN), PSII chlorophyll fluorescence (PItot), non-structural carbohydrate concentrations (NSC; soluble sugars, starch) and carbon isotope signatures were measured in leaves throughout the growing season. Pre-dawn water potentials (ψpd), gS, ci, AN and PItot decreased as drought progressed, and the concentration of soluble sugars increased at the expense of starch. Carbon isotopes in soluble sugars (δ13CS) showed a distinct increase under drought, suggesting, together with decreased ci, stomatal limitation of AN. Drought effects on ψpd, ci and NSC disappeared shortly after re-watering, while full recovery of gS and AN was delayed by one week and full recovery of PItot by two weeks. The fast recovery of NSC was reflected by a rapid decay of the drought signal in δ13C values, indicating a rapid turnover of assimilates and a reactivation of carbon metabolism. After recovery, the previously drought-exposed saplings showed a stimulation of AN and a trend towards elevated starch concentrations, which counteracted the previous drought limitations. Overall, our results suggest that the internal water relations of beech saplings and the physiological activity of leaves are restored rapidly after drought release. In the case of AN, stimulation after drought may partially compensate for limitations on photosynthetic activity during drought. Our observations suggest high resilience of beech to drought, contradicting the general belief that beech is particularly sensitive to environmental stressors.